2014
DOI: 10.2478/folmed-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Retroaortic Left Renal Vein Abnormalities in Cross-Sectional Imaging

Abstract: Preoperative knowledge of LRV abnormalities facilitates the safe performance of surgery and reveals the clinical symptoms. It is easy to see LRV and its drainage way on routine CT and MR imagings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The results of our study show that the incidence of total LRV variations in the Turkish population is similar to that of other races (6,7,9,16,17).…”
Section: Discussionsupporting
confidence: 77%
“…The results of our study show that the incidence of total LRV variations in the Turkish population is similar to that of other races (6,7,9,16,17).…”
Section: Discussionsupporting
confidence: 77%
“…Retroaortic left renal veins are reported to be present in 2–9% of living kidney donors [9-11]. Our hospital data match these results, with 11 patients (4.98%) who had a retroaortic left vein.…”
Section: Discussionsupporting
confidence: 84%
“…The authors have found the prevalence of CALRV as 5.5%, and that of RALRV as 4.6% (10). Sahin et al found the prevalence of LRV anomalies as 2.3%, that of RALRV as 2%, and that of CALRV as 0.3% (12). Ayaz et al reported the prevalence of LRV variations as 5.85%, that of CALRV as 3.15%, and that of RALRV as 2.70%.…”
Section: Discussionmentioning
confidence: 99%